Speech Matters : On Lying, Morality, and the Law - Shiffrin, Seana Valentine (Book collections on Project MUSE., 2014)
"To understand one another as individuals and to fulfill the moral duties that require such understanding, we must communicate with each other. We must also maintain protected channels that render reliable communication possible, a demand that, Seana Shiffrin argues, yields a prohibition against lying and requires protection for free speech. This book makes a distinctive philosophical argument for the wrong of the lie and provides an original account of its difference from the wrong of deception. Drawing on legal as well as philosophical arguments, the book defends a series of notable claims-that you may not lie about everything to the "Murderer at the Door," that you have reasons to keep promises offered under duress, that lies are not protected by free speech, that police subvert their mission when they lie to suspects, and that scholars undermine their goals when they lie to research subjects."